Dietary carbohydrate‐to‐lipid ratios modulate juvenile hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatus): Effects on growth, serum biochemistry, intestinal digestion and hepatic metabolism of glucose and lipid. (6th May 2021) - Chen, Guofeng; Qian, Jiahao; Liu, Hongyu; Tan, Beiping; Dong, Xiaohui; Yang, Qihui; Chi, Shuyan; Zhang, Shuang
Abstract: A 56 day feeding trial was conducted to study effects of different carbohydrate‐to‐lipid (CHO.L −1 ) ratios on growth, serum biochemistry, intestinal digestion and hepatic metabolism of glucose and lipid in juvenile hybrid grouper ( Epinephelus fuscoguttatus × ♂ E .  lanceolatus ). Results showed that moderate CHO.L −1 ratio resulted in better growth performance ( p  < .05). In serum, glucose, insulin and alanine aminotransferase were enhanced as CHO.L −1 ratios increased, whereas cholesterol was reduced ( p  < .05). Increased CHO.L −1 ratios resulted in raised activity of amylase and reduced activity of lipase in gut ( p  < .05). Gene expression related to glucose transporters improved ( p  < .05). Enzyme activity and gene expression involved in hepatic glycolysis improved in a limited manner, whereas enzyme activity and gene expression related to hepatic gluconeogenesis and lipolysis were inhibited in high CHO.L −1 ratio group. Enzyme activity of hepatic lipogenesis showed an elevated trend, including acetyl‐CoA carboxylase and fatty acid synthase ( p  < .05). In conclusion, different dietary CHO.L −1 ratios affected growth, serum biochemistry, intestinal digestion and hepatic metabolism of glucose and lipid in grouper. Moreover, juvenile grouper could utilize diet containing moderate CHO.L −1 ratio.